Are perception and adaptation to climate variability and change of cowpea growers in Mali gender differentiated? - Diarra, Fatimata Bintou; Ouédraogo, Mathieu; Zougmoré, Robert B.; Partey, Samuel T.; Houessionon, Prosper; Mensa, Amos (Springer, 2021)
Understanding the gender dimension of climate change perception and choice of adaptation strategies is crucial for policy recommendations that foster the development and integration of gender-responsive climate-smart agricultural interventions into agricultural development programs. This study determined the differences in the perception and choice of adaptation strategies between men and women farmers in Cinzana in the Segou region of Mali. The study used questionnaire interviews involving 260 farmers (49% women) and focus group discussions for data collection. Data were analyzed using descriptive statistics and multinomial logit model to understand the determinants of the level of adoption of adaptation strategies. The results showed that, irrespective of gender, majority of farmers perceived climate change as extended period of droughts, shortened duration of rains, increased frequency of strong winds and increased day and night temperatures. While climate change perception was similar between men and women, choice of adaptation strategies differed significantly in most instances. Women farmers were generally low adopters of crop and varieties-related strategies, soil and water conservation technics (contour farming, use of organic manure), etc., compare to men. Notably, being the household head, age and the availability of free labor were found to positively increased farmers’ probability of adopting many adaptation strategies. The study recommends improving women’s access and control of production resources (land, labor) as means to improving their adoption of adaptation strategies.